Effect of varying doses of dexmedetomidine added to dexamethasone-enhanced TAPB for post-cesarean pain management - Gu, Yang; Yang, Fan; Bao, Jiamin; Wang, Fa; Tian, Biyun; Sun, Hui; Li, Ningkang; Ye, Qingshan (Frontiers in Medicine, 2025)
BackgroundThe management of post-cesarean pain exhibits considerable variation across different regions and hospitals, with a prevalent tendency to utilize opioid medications as the primary analgesic approach. This study investigates the impact of different doses of dexmedetomidine combined with dexamethasone as an adjunct to transversus abdominis plane block (TAPB) on the analgesic efficacy and quality of recovery following cesarean section.MethodsIn this prospective randomized clinical trial, 90 patients scheduled for cesarean section were randomly assigned in a 1:1:1 ratio to receive postoperative TAPB with one of three solutions: 8 mg dexamethasone with 0.375% ropivacaine (Group C), 0.5 μg/kg dexmedetomidine with 8 mg dexamethasone and 0.375% ropivacaine (Group D1), or 1 μg/kg dexmedetomidine with 8 mg dexamethasone and 0.375% ropivacaine (Group D2). The primary outcome measures were the VAS scores for rest and movement at 6, 12, 24, and 48 h post TAPB, as well as the incidence of moderate to severe pain.ResultsPostoperative VAS scores demonstrated distinct patterns between rest and dynamic pain. At rest, no significant differences were observed among groups C, D1, and D2 at any time point (6–48 h; all p > 0.05). For dynamic pain, group C exhibited higher median scores than D1 and D2 at 12 h [3.00 (IQR 2.00–4.00) vs. 1.00 (1.00–3.00), median difference 1.00 (95% CI 1.00–2.00); p = 0.001; vs. 2.00 (1.00–3.00), difference 1.00 (0.00–2.00); p = 0.003] and 24 h [4.00 (3.00–4.00) vs. D1: 3.00 (2.00–3.00), difference 1.00 (0.00–1.00); p < 0.001; vs. D2: 2.00 (2.00–3.00), difference 1.00 (1.00–2.00); p = 0.009]. By 48 h, D2 showed the lowest dynamic pain scores [1.00 (1.00–2.00) vs. C: 3.00 (2.00–3.00); difference 1.00 (1.00–1.00); p = 0.001]. Moderate-to-severe dynamic pain incidence differed significantly at 12 h (C: 26.7%; D1: 13.3%; D2: 3.3%; p = 0.04) and peaked in group C at 24 h [53.3% vs. D1: 13.3% (risk ratio 7.43, 95% CI 2.08–26.55; p = 0.002) and D2: 10.0% (risk ratio 10.29, 2.56–41.37; p = 0.001)]. No intergroup differences were observed for resting pain or dynamic pain at 48 h. Groups D1 and D2 showed no significant differences in outcomes at any time point.ConclusionAdding dexmedetomidine and dexamethasone to ropivacaine for TAPB can improve post-cesarean section pain conditions.Clinical trial registrationhttps://clinicaltrials.gov/, ChiCTR2400081531.